A transmutação da personagem Lolita de Nabokov da literatura para as telas - Silva, Jardas de Sousa (2015)
This dissertation analyzes the translation of Lolita character, by Vladimir Nabokov, to the eponymous film made in 1997, directed by Adrian Lyne. In the novel Lolita (1955), the man character is a 12 year-old girl whose life changed when she had started being stalked by Humbert Humbert, a grown-up and much more experienced man who soon becomes stepfather of hers. By facing this situation, Lolita is seen as a character who has some behavioral traits that give us an ideia of ambivalence about her presentation in the novel. Many of Lolita‟s attitudes can be interpreted either the result of a childish naivety or as kinds of games created by a cunning mind. In this study, we investigate, specifically, the strategies used by the director to transmute Lolita‟s ambiguities from the novel Lolita to the cinema. Our hypothesis is that the protagonist as a symbol of nymphet, that is, the seductive girl, was the most emphasized aspect in the film adaptation due to the inherent issues both related to the director‟s poetic and the types of Hollywood productions in the nineties. As theoretical background, we take the Even-Zohar‟s assumptions (1978), on the theory of polysystem, and the Toury‟s ones (1995), which refer to translation studies with emphasis on cultural factor, considering the influence of the target culture has on the translation process. We also work with the concept of rewriting by Lefevere (2007), which emphasizes the historical and cultural context of the translated texts. On the relationship between literature and film, we deal with the studies by Cattrysse (1992), Stam (2008) and Xavier (2003). Finally, we also rely on postulates by Candido (2007) and Gomes (2007), regarding to the construction of literary and filmic characters, and Lolita previous studies, such as those by Agueros (2005) and Lazarin (2010). The results pointed that the strategies to present the character Lolita on screen intensify the myth of the nymph, the femme fatale, which permeates its name from its first translations. Therefore, in the adaptation, Lolita can be interpreted as the anti-heroine of her own story while Humbert becomes the passionate hero.